Surgical treatment options in chronic subdural hematoma: A literature review - Husodo, Kharisma Ridho; Suryonurafif, Akhmad (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2024)
Chronic subdural hematoma (cSDH) is one of the most common neurosurgery cases in daily practice. Chronic subdural hematoma is clot formation in the subdural space between the dura mater and the arachnoid layer. Due to its progression, clinical presentation of cSDH mostly appears 4 to 8 weeks after a traumatic brain injury. It is the duration needed for the hematoma to grow large enough to cause severe neurological symptoms such as decreased consciousness, hemiparesis, and other signs and symptoms of increased intracranial pressure. There are three main options to treat cSDH. Conservative treatment, surgical treatment, and embolization of the middle meningeal artery (MMA) are widely used to manage this condition. Predominantly, surgical treatments used by neurosurgeons around the world are craniotomy, burr hole (BH) craniostomy, and twist drill (TD) craniostomy. Each of these procedures has advantages and disadvantages. This literature review aimed to consider the characteristics of several treatment options for cSDH and their technique. This review recommends BH craniotomy due to its benefits based on its complication and recurrence rates. Burr Hole craniotomy has a lower complication rate than craniotomy and a lower recurrence rate than TD craniotomy. Twist drill craniotomy is selectively considered for certain patients since this procedure is commonly performed at the bedside without general anesthesia. Craniotomy is recommended as a treatment option for persistent recurrence of cSDH or patients with massive subdural hematoma.